FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS TIDUR PADA LANSIA DI KELURAHAN LAHENDONG TOMOHON SELATAN - Sarayar, Christiane Prisilia; Pondaa, Angelia; Pondaag, Linni (JURNAL ILMIAH KESEHATAN MANADO, 2024)
As people get older, their sleep needs and patterns will changes of an aging, but this varies greatly between individuals. After the age of 60 years and above, night sleep tends to be shorter, lighter and disturbed by several awakenings. The Centers for Disease Control and Prevention (CDC) in 2024 recommends that the elderly get 7-8 hours of sleep every day. In addition to quantity, sleep quality is necessary to get physical, mental and emotional benefits. Sleep quality, sleep duration, sleep satisfaction and consistency are important components of meeting human sleep needs. Indonesia since 2021 has entered an ageing population structure, around 1 in 10 residents are elderly. In North Sulawesi, based on statistical data on the elderly in 2023, 13.70% of the population is >60 years old, and in Tomohon City, the number of elderly people in 2022 is 14,394 people This study was conducted to determine the factors that affect the quality of sleep of the elderly in Kelurahan Lahendong, Tomohon City in 2024, using a quantitative method with a cross-sectional design. The study involved 87 respondents and analyzed the relationship between age, gender, and history of chronic diseases and sleep quality in the elderly. The results showed that 57.5% of the elderly had poor sleep quality, and based on bivariate analysis, it showed that there was a relationship between age, gender, and history of chronic diseases with the sleep quality of the elderly. These findings could be the source for further research on improving sleep quality in the elderly.